Employee Motivation and Performance Models - Ma’ruf, Farid; Hadari, Ita Reinita; Amalia, Dini (International Review of Management and Marketing, 2019)
This study aims to determine the effect of empowerment, interpersonal communication and work involvement on performance with work motivation as a mediating variable. The sample in this study amounted to 300 employees of PT. Humanindo Jakarta. Analysis of the data used is path analysis. The results showed that there was a direct influence on empowerment and work involvement on employee performance, but interpersonal communication was not significant. The indirect effect on employee performance through work motivation shows that interpersonal communication is significant, while empowerment and work involvement are not significant. Keywords: Empowerment, Interpersonal Communication, Work Engagement, Work Motivation, Employee Performance. JEL Classifications: O32, M54, N75 DOI: https://doi.org/10.32479/irmm.8811